1997
DOI: 10.1093/hmg/6.11.1771
|View full text |Cite
|
Sign up to set email alerts
|

Frataxin is Reduced in Friedreich Ataxia Patients and is Associated with Mitochondrial Membranes

Abstract: Friedreich ataxia is a progressive neurodegenerative disorder caused by loss of function mutations in the frataxin gene. In order to unravel frataxin function we developed monoclonal antibodies raised against different regions of the protein. These antibodies detect a processed 18 kDa protein in various human and mouse tissues and cell lines that is severely reduced in Friedreich ataxia patients. By immunocytofluorescence and immunocytoelectron microscopy we show that frataxin is located in mitochondria, assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
496
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 675 publications
(524 citation statements)
references
References 33 publications
20
496
1
2
Order By: Relevance
“…It should be noted that this individual (GM 16216) had the smallest amount of total expanded GAA triplet repeats within the FA patient cohort and it only overlapped a single FA carrier -the one that has the most GAA repeats (GM 15849) ( Table 2). Finally, we demonstrate that there is an inverse correlation between the number of triplet repeats in the frataxin gene and the levels of the protein, which is consistent with current understanding of the pathology of FA and GAA repeats [4,15]. Previous studies which quantified either frataxin protein levels by Western blot analysis or measured frataxin mRNA levels by real time PCR have found that frataxin levels in FA patients are between 6% and 30% of controls for protein levels and between 13% and 30% for mRNA levels [2,17].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…It should be noted that this individual (GM 16216) had the smallest amount of total expanded GAA triplet repeats within the FA patient cohort and it only overlapped a single FA carrier -the one that has the most GAA repeats (GM 15849) ( Table 2). Finally, we demonstrate that there is an inverse correlation between the number of triplet repeats in the frataxin gene and the levels of the protein, which is consistent with current understanding of the pathology of FA and GAA repeats [4,15]. Previous studies which quantified either frataxin protein levels by Western blot analysis or measured frataxin mRNA levels by real time PCR have found that frataxin levels in FA patients are between 6% and 30% of controls for protein levels and between 13% and 30% for mRNA levels [2,17].…”
Section: Discussionsupporting
confidence: 86%
“…Previously, frataxin protein levels could only be estimated by Western blot, which is cumbersome and semi-quantitative at best [15]. In contrast, the lateral flow immunoassay described here is quantitative, accurate and reproducible, with low intra and inter-assay error throughout a wide working range.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…F riedreich's ataxia (FRDA) is a neurodegenerative disorder that arises from a genetic deficit of the mitochondrial iron chaperone protein, frataxin (1)(2)(3). The progressive loss of coordination of limb movements, dysarthria, nystagmus, scoliosis, and diabetes characteristic of FRDA usually manifest before adolescence.…”
mentioning
confidence: 99%